The Penilaian Sumber Daya Air (Water Resources Assessment) Sub DAS Cirasea, Kabupaten Bandung - Dhea Fitria; Syafrudin; Anik Sarminingsih (Postgraduate, University of Mataram, 2025)
The phenomena that often occur in the Cirasea Sub-DAS are floods in the rainy season and droughts in the dry season. Climate change, land use changes, population growth and industrialization have put significant pressure on the availability of water resources in the Cirasea Sub-DAS. The purpose of this study is to gain a better understanding of water resources and their management in the area. The research method used in this study is descriptive with a quantitative approach. Water availability is calculated using the HEC-HMS simulation and water needs are calculated using the formula approach published by the Ministry of Environment, 2014. A comprehensive analysis of water availability and the risk of water scarcity is assessed using HEC-HMS. Calibration and validation are also carried out to determine the suitability between field discharge data (measured) and the calculation results using HEC-HMS (calculated). The calculation results of the mainstay discharge of the Upper Citarum River referring to SNI 6738-2015, obtained the mainstay discharge of the Upper Citarum River Q80 of 2.3 m3/second, Q90 of 1.52 m3/second and Q95 of 1.1 m3/second. This research can provide a significant contribution in optimizing the carrying capacity and management of water resources in the Cirasea Sub-DAS area. The results can also be used to help determine strategies and planning for future water resource management.